Psychological factors, digital behaviors, and lifestyle correlates of insomnia among university students: A literature review - Purdani, Kartika Setia; Ridho, Muhammad; Safrudin, Bachtiar; Alamsyah, Fachmi; Zain, Najla Dalilah Ramadhania; Wati, Putri Sintya; Lestari, Shinta Dwie; Dewi, Cindy Maharani; Cholifah, Winna Noor; Saputra, Bagas (Lentera Perawat, 2026)
Background: Insomnia is a prevalent sleep problem among university students and is increasingly linked to psychological distress, intensive digital engagement, and unhealthy lifestyle patterns, all of which may impair academic functioning and well-being. Existing evidence is fragmented across disciplines, making an integrated synthesis necessary for nursing and campus health practice. Objective: This literature review aimed to synthesize evidence on psychological factors, digital behaviors, and lifestyle correlates associated with insomnia among university students. Methods: A structured literature review was conducted using predefined eligibility criteria, staged screening, and standardized data extraction. The review included quantitative studies on university students published between 2021 and 2025 in Indonesian or English, with insomnia-related outcomes and relevant correlates. From 166 identified records, 10 studies met the inclusion criteria and were narratively synthesized across three analytic domains: psychological factors, digital behaviors, and lifestyle variables. Results: Across the 10 included studies, stress and anxiety emerged as the most consistent correlates of insomnia severity. Digital factors—particularly intensive social media use, smartphone addiction, and problematic gadget use—were also repeatedly associated with insomnia, with several studies suggesting mediating psychological pathways (e.g., FoMO and phone dependence). Lifestyle findings were partially heterogeneous: some studies identified significant associations for coffee intake and physical activity, whereas others reported non-significant results for similar variables. Most student participants experienced mild-to-moderate insomnia, indicating a common but often underrecognized burden. Conclusion: Insomnia among university students is a multidimensional condition influenced by interacting psychological, digital, and lifestyle factors. The most robust evidence supports stress, anxiety, and intensive digital behavior as primary correlates, while lifestyle and environmental effects appear context-dependent.